What's Driving Sustainable Energy Consumption? A Survey of the Empirical Literature - Rolf Wüstenhagen; Joachim Schleich; Klaus Rennings; Stefanie Heinzle; Bettina Brohmann (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
The focus of the paper is on the individual decision of energy consumers, and it's relation to sustainable consumption. Consumer behavior is based on individual decisions, but it depends largely on supply-side measures and an appropriate infrastructure (e.g. the availability of energy-efficient household equipment) and on socio-political factors (e.g. if systems of emissions trading or eco-labels exist). We derive some hypotheses on the determinants of sustainable energy consumption in residential buildings from a review of the empirical literature on the diffusion of energy efficient activities. While there is agreement on a lot of factors, the role of environmental attitudes and environmental behavior remains uncertain. Thus research needs are derived respectively. Finally, we specify these hypotheses for three specific technologies of sustainable energy consumption: Domestic appliances, micro-power and green electricity.
Keywords: Q01; Q41; 330; Sustainable consumption; consumer behaviour; domestic appliances; micro-power; green electricity